2021
DOI: 10.1038/s41598-021-93251-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile in HCV patients treated with direct-acting antivirals: a systematic review and meta-analysis

Abstract: Although direct-acting antivirals are very effective and safe drugs, several authors have reported the alteration of lipid profile during and after anti-HCV therapy suggesting a potential impact on the risk of cardiovascular events. We performed a systematic review and meta-analysis of observational studies to investigate the magnitude and temporal trend of lipid profile changes in DAA treated patients. All selected studies included data on lipid profile before starting therapy and at least one follow-up asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Recent studies among predominantly genotype 1 HCV-infected patients suggest an effect of DAAs therapy on cholesterol and triglyceride levels [48,49]. Thus, DAAs therapy induce elevated triglycerides and cholesterol levels [50,51]. In line with these reports, we observed a significant increase in triglyceride levels (124.03 ± 113.49 mg/dL vs. 153.78 ± 94.53 mg/dL) and in cholesterol levels (191.61 ± 67.19 mg/dL vs. 216.52 ± 50.85), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies among predominantly genotype 1 HCV-infected patients suggest an effect of DAAs therapy on cholesterol and triglyceride levels [48,49]. Thus, DAAs therapy induce elevated triglycerides and cholesterol levels [50,51]. In line with these reports, we observed a significant increase in triglyceride levels (124.03 ± 113.49 mg/dL vs. 153.78 ± 94.53 mg/dL) and in cholesterol levels (191.61 ± 67.19 mg/dL vs. 216.52 ± 50.85), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, DAA therapy did not significantly influence serum TG levels [ 3 ]. Similarly, serum TG levels were comparable between HCV-infected patients and noninfected controls [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 On the contrary, other studies showed no effect of directly acting antiviral (DAA) therapy on triglyceride levels. 5 …”
Section: Discussionmentioning
confidence: 99%